Language, Power, and Resistance : Mainstreaming Deaf Education - Mathews, Elizabeth S. (Book collections on Project MUSE., 2017)
"The current policy ofeducating d/Deaf and h/Hard of hearing (DHH) students in a mainstream setting, rather than inthe segregated environments of deaf schools, has been portrayed as a positive step forward in creating greater equality for DHH students. In Language, Power, and Resistance, Elizabeth S. Mathews explores this claim through qualitative research with DHH children in the Republic of Ireland, their families, their teachers, and their experiences of the education system. While sensitive to the historical context of deaf education, Mathews focuses on the contemporary education system and the ways in which the mainstreaming agenda fits into larger discussions about the classification, treatment, and normalization of DHH children. The research upon which this book is based examined the implications that mainstreaming has for the tensions between the hegemonic medical model of deafness and the social model of Deafness. This volume explores how different types of power are used in the deaf education system to establish, maintain, and also resist medical views of deafness. Mathews frames this discussion as one of power relations across parents, children, and professionals working within the system. She looks at how various forms of power are used to influence decisions, to resist decisions, and to shape the structure and delivery of deaf education. The author's findings are a significant contribution to the debates on inclusive education for DHH students and will resonate in myriad social and geographic contexts"--